Psychosocial Problems Among Primary School Children in Thailand During the COVID-19 Pandemic, 2022 - Pudpong N; Julchoo S; Sinam P; Uansri S; Kunpeuk W; Suphanchaimat R (Dove Medical Press, 2023)
Nareerut Pudpong,1 Sataporn Julchoo,1 Pigunkaew Sinam,1 Sonvanee Uansri,1 Watinee Kunpeuk,1 Rapeepong Suphanchaimat1,2 1International Health Policy Program, Ministry of Public Health, Nonthaburi, Thailand; 2Division of Epidemiology, Department of Disease Control, Nonthaburi, ThailandCorrespondence: Rapeepong Suphanchaimat, International Health Policy Program, Ministry of Public Health, Nonthaburi, Thailand, Tel +66815446966, Email rapeepong@ihpp.thaigov.netBackground: During the COVID-19 pandemic, primary school children are particularly vulnerable as restriction measures have caused a huge impact on their health and well-being. This study aims to assess the prevalence of mental health among primary school children in Thailand during the COVID-19 pandemic and identify factors associated with psychosocial problems.Methods: A survey was conducted among 701 Thai parents of primary school children from January to March 2022 - when teaching modalities between onsite and online learning were alternated. Parents were requested to assess the mental health of their youngest child at primary school age level. Psychosocial problems were measured by the Strengths and Difficulties Questionnaire (SDQ) with a total score of 40, based on 4 domains (emotion, behavior, hyperactivity, and relationship). Independent variables included (1) parental/household factors, (2) children characteristics, and (3) online learning-related issues. The dependent variable was the prevalence of children with a total score of 14- 40, which indicates at risk and/or having mental health problems. The analysis was performed using logistic regression model.Results: Thai parents reported that 41.1% of children had psychosocial problems. Children in a single-parent family (adjusted odds ratio [AOR] = 1.7; 95% confidence interval (CI) = 1.1- 2.8), male children (AOR = 1.7, 95% CI = 1.2- 2.4), and children who did not receive adequate assistance for online learning from their parents (AOR = 2.1, 95% CI = 1.1- 4.0) significantly faced greater odds of mental health problems.Conclusion: The prevalence of Thai primary school children confronting psychosocial difficulties during the COVID-19 pandemic increased, with significant concern. Public health interventions that aim to protect the mental health of primary school children during the pandemic should be introduced and targeted male children and those living with a single parent. Social support that facilitates online learning for children whose parents have limited capacity in supporting them should be implemented.Keywords: mental, health, primary school, children, COVID-19, Thailand